Loss Aversion Bias in Working Capital Management and Performance of Small and Medium Enterprises (SMEs): The perspectives of Ghanaian SME Managers - Jeff, Lamptey; Asri, Marsidi (Human Resource Management Academic Research Society, 2020)
We examine Loss aversion bias in working capital management and performance of Small and medium-sized enterprises (SMEs) in Accra, Ghana. Our study adopts a qualitative case study approach and in-depth interviews to obtain data from thirty-five (35) Owner-managers. This research shows that SME managers(owners) are loss aversion as they evaluate financial outcomes by thinking about loss and profits and use profits in most financial decision thereby prone to fear of loss. Moreover, SMEs managers (owners) subjected to enormous fear tend to be highly loss averse over loss (uncertain gain) and risk averse. While managers(owners) with less fear are low loss averse over profits and risking seeking. By implication, low loss averse SME managers(owners) tend to perform better than highly loss averse managers who underinvest in working capital in inventory, resulting in decreased profit margins. Thus, we conclude SMEs manager’s loss aversion matters in working capital management and performance